2022
DOI: 10.1039/d2ma00152g
|View full text |Cite
|
Sign up to set email alerts
|

Surface-mediated twin polymerisation of 2,2′-spirobi[4H-1,3,2-benzodioxasiline] on multi-walled carbon nanotubes, polyacrylonitrile particles and copper particles

Abstract: Application of twin polymerization by a base-catalysed, surface-mediated coating procedure is shown on different templates. Post-polymerization treatment leads to microporous shells on MWCNTs, N-doped carbon particles, and copper particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 94 publications
1
28
0
Order By: Relevance
“…A mechanism of bonding states of the pyrrolidine amine base on the Cu particles is shown in Scheme 9. [98] High-angle annular dark-field single transmission electron microscopy (= HAADF-STEM) confirmed that the appropriate phenolic resin-silica hybrid layers are between 20-120 nm on the MW-CNTs (Figure 6). The thickness of the corresponding layers can be controlled by the amount of the twin monomer added: It increases with growing initial monomer concentration from ca.…”
Section: Orthosilicates and Oxasilanesmentioning
confidence: 85%
See 4 more Smart Citations
“…A mechanism of bonding states of the pyrrolidine amine base on the Cu particles is shown in Scheme 9. [98] High-angle annular dark-field single transmission electron microscopy (= HAADF-STEM) confirmed that the appropriate phenolic resin-silica hybrid layers are between 20-120 nm on the MW-CNTs (Figure 6). The thickness of the corresponding layers can be controlled by the amount of the twin monomer added: It increases with growing initial monomer concentration from ca.…”
Section: Orthosilicates and Oxasilanesmentioning
confidence: 85%
“…[96] Another application is given by the surface-mediated TP of 1 on multi-walled carbon nanotubes (= MW-CNTs), copper metal particles and polyacrylonitrile particles. [98] The group of Mehring confirmed the possibility of using base-catalyzed TP of the twin monomer 1 to coat these substrates with a nanostructured phenolic resin-silica hybrid material layer, whereby the respective coating procedure was carried out as seed polymerization by applying base-modified substrates as the catalyst in a slurry of diisopropylnaphthalene. The formation of the successful coating was proven by IR and solid-state 13 C{ 1 H} and 29 Si{ 1 H} CP-MAS NMR spectroscopy.…”
Section: Orthosilicates and Oxasilanesmentioning
confidence: 99%
See 3 more Smart Citations